PENGGUNAAN INDEKS PENCEMARAN LOGAM BERAT DALAM SEDIMEN DI WILAYAH PESISIR: STUDI KASUS SEGARA ANAKAN CILACAP JAWA TENGAH - Triyoni Purbonegoro (OSEANA, 2022)
The concentration of heavy metals in the water column does not necessarily reflect the actual pollution of coastal waters. This is because the concentrations of heavy metals in water columns are generally lower than in sediments. Heavy metal contamination in sediments is a serious threat to coastal ecosystems and has become a major concern for the community. For better management of coastal ecosystems, stakeholders need information on environmental conditions that is easy to understand. The pollution index is very useful for processing, analyzing, and translating ‘raw’ environmental data into easily understood information. The CF index is useful for determining the pollution status of single metal, while the PLI index is useful for determining the pollution status of several heavy metal contaminants in sediments. The Igeo index determines the level of pollution by taking into account the effects of variations in the earth's layers (lithosphere), while the EF index determines the level of heavy metal enrichment and determines whether the enrichment is natural or comes from human activities (anthropogenic). Finally, the PERI index determines the ecological risk caused by the contamination of several metals by taking into account the toxic response of each metal.